Emotional Intelligence in Islamic Religious Education Learning: Approach, Implementation, and Impact on Student Character Development - Susanti, Riska; Nukman, Muhammad (Journal of Education and Computer Applications, 2024)
The application of emotional intelligence in Islamic Religious Education learning, with a focus on the approach, implementation, and impact on the development of student character. Emotional intelligence is considered crucial in this context because it affects how students interact with Islamic religious materials, fellow students, and the school environment. The implementation of emotional intelligence in learning is expected to improve students' understanding of religious values, as well as strengthen their character in everyday life. This study highlights the importance of integrating emotional intelligence in the context of Islamic religious education to support the formation of holistic and ethical personalities in future generations. The results of the study indicate that the development of emotional intelligence in Islamic Religious Education learning has a positive impact on the formation of student character. Students become better able to manage emotions, empathize, and interact well. This contributes to increased academic achievement, prosocial behavior, and psychological well-being of students. Thus, emotional intelligence is an important component in Islamic Religious Education learning to realize the goals of character education.